2021
DOI: 10.1097/md.0000000000027250
|View full text |Cite
|
Sign up to set email alerts
|

Effect of baduanjin on the fall and balance function in middle-aged and elderly people

Abstract: Background: The risk of fall seriously affects the health and quality of life of the middle-aged and elderly people, especially the injury and disability caused by fall of the middle-aged and elderly people, which imposes a huge burden on family and social medical care. Baduanjin exercise may be an effective intervention to enhance the muscle strength and stability of lower limbs, improve the balance ability and gait of middle-aged and elderly people, reduce the incidence of falls, improve the qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…We conclude that Baduanjin exercise positively affects gait in patients with mild to moderate PD. Xiao et al (2021) analyzed 8 randomized clinical trial studies on Baduanjin, and they believed that Baduanjin can improve the balance function in middle-aged and elderly people and reduce the fall rate.…”
Section: Discussionmentioning
confidence: 99%
“…We conclude that Baduanjin exercise positively affects gait in patients with mild to moderate PD. Xiao et al (2021) analyzed 8 randomized clinical trial studies on Baduanjin, and they believed that Baduanjin can improve the balance function in middle-aged and elderly people and reduce the fall rate.…”
Section: Discussionmentioning
confidence: 99%
“…Since previous studies have demonstrated a link between sarcopenia and several adverse health outcomes like falls and fractures [1,3], and Baduanjin exercise has advantages in improving balance, gait and physical function and reducing falls [14,15,[25][26][27][28]. In order to provide another effective and safe exercise intervention for elderly people, who lack access or motivation to participate in a rigorous exercise program, to combat sarcopenia and minimize such adverse events, we really hope regular Baduanjin exercise can be a promising choice for them.…”
Section: Discussionmentioning
confidence: 99%
“…Baduanjin only has eight simple forms, which are linked together with smooth transitions from one form to the next [2]. A low demand for physical ability and training space makes it a home-based training for promoting physical health, even for frail people who are at risk of falls [3]. Baduanjin is also widely used in patient rehabilitation for stroke, Parkinson's disease, knee osteoarthritis, diseases of the patellar extremity, etc [4].…”
Section: Introductionmentioning
confidence: 99%